2003
DOI: 10.1108/03090560310498813
|View full text |Cite
|
Sign up to set email alerts
|

Internal marketing issues and challenges

Abstract: This commentary discusses the key issues and challenges that face internal marketing research and for the future development of the concept and philosophy. Issues addressed include: the link between employee satisfaction and organisational performance; the need for research on how inter-functional co-ordination can be achieved for the effective implementation of marketing strategies; the need for relationship marketing perspective in internal marketing; the need for research in internal communication strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
219
1
17

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(259 citation statements)
references
References 14 publications
10
219
1
17
Order By: Relevance
“…Ahmed and Rafiq (2000) have introduced price and payments, sale promotion (education, empowerment and communications), working place or environment and process (job products) as indices of internal marketing by applying of the expression "internal marketing mix". In another study about examining of service organizations in England they have used factors like training of the human resources, empowerment, communications, team activities, employees' participation in determining of the organization's perspective as the important factors in measuring of internal marketing (Ahmed and Rafiq, 2003). Galpin (1997) has done a study in Malaysia about internal marketing and has used indices of organizational plans in the form of adhocracy, strategic rewards, internal communications, education and development, selection, reward systems, empowerment and processes for measurement and evaluation of internal marketing.…”
Section: Internal Marketingmentioning
confidence: 99%
“…Ahmed and Rafiq (2000) have introduced price and payments, sale promotion (education, empowerment and communications), working place or environment and process (job products) as indices of internal marketing by applying of the expression "internal marketing mix". In another study about examining of service organizations in England they have used factors like training of the human resources, empowerment, communications, team activities, employees' participation in determining of the organization's perspective as the important factors in measuring of internal marketing (Ahmed and Rafiq, 2003). Galpin (1997) has done a study in Malaysia about internal marketing and has used indices of organizational plans in the form of adhocracy, strategic rewards, internal communications, education and development, selection, reward systems, empowerment and processes for measurement and evaluation of internal marketing.…”
Section: Internal Marketingmentioning
confidence: 99%
“…The detailed literature review showed that the benefits of successfully implemented internal marketing activities include such consequences (Ahmed and Rafiq, 2003;Arnett et al 2002: 87-89;Atlay Işık, 2011: 141-142;Dunne and Barnes, 2000: 196;Greene et al 1994: 5-8;Gronroos, 1981;Heskett et al 1994;Mishra, 2010: 189;Ting, 2011: 360;Varey, 1995: 46): -decreasing the rate of personnel turnover, -creating customer-conscious employees, -improving employee commitment to the organization, -reducing the barriers between departments, -ensuring effective overall communication, -promoting employees' job satisfaction and motivation, -facilitating organizational growth and development, -improving ability to implement change within the organization, -improving service quality, -enhancing customer satisfaction and customer loyalty, and -achieving and sustaining competitive advantage.…”
Section: Source: Authorsmentioning
confidence: 99%
“…Internal marketing was defined as a planned effort using marketing like approach to overcome organizational resistance, to change and to align, motivate, and inter-functionally co-ordinate and integrate employees towards the effective implementation of corporate and functional strategies in order to deliver customer satisfaction through the process of creating motivated and customer-orientated employees. Internal marketing focuses on people inside organizational boundaries and places emphasis on the satisfaction of employee needs (Ahmed and Rafiq, 2003). Davis (2001) suggested that internal marketing can bridge the gap between the different internal constituencies and establishing cooperation among them.…”
Section: Concept Of Internal Marketingmentioning
confidence: 99%